2006
DOI: 10.2166/wpt.2006.066
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption characteristics of reactive dye onto dried activated sludge

Abstract: This study examined the removal of reactive dye onto dead cells in activated sludge collected from the municipal sewage treatment plant in Suyoung, Pusan. The biosorption of reactive dye from aqueous solutions using the activated sludge was studied using a batch system with respect to the initial pH, temperature, amount of adsorbent and the pre-treatment of the adsorbent. Both the Freundlich and Langmuir isotherm models could describe the adsorption equilibrium of the reactive dye onto the activated sludge wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…An increase in initial dye concentration leads to an increase in the adsorption uptake of MB on MSN AP . This is due to an increase in the driving force of the concentration gradient, as an increase in the initial dye concentration [27]. Fig.…”
Section: Performance Of Mesostructured Silica and Effect Of Initial Cmentioning
confidence: 94%
“…An increase in initial dye concentration leads to an increase in the adsorption uptake of MB on MSN AP . This is due to an increase in the driving force of the concentration gradient, as an increase in the initial dye concentration [27]. Fig.…”
Section: Performance Of Mesostructured Silica and Effect Of Initial Cmentioning
confidence: 94%
“…A high level of worldwide production and extensive use of dyes generate colored wastewaters, which are environmental pollutants [1]. Dyes pose serious environmental problems because of their color, low biochemical oxygen demand (BOD), and high chemical oxygen demand (COD) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Activated sludge was dried at 105 °C to a constant weight and sieved to < 205 m for use as an adsorbent in a study for removal of Rhodamine-B dye (Ju et al, 2006). The results indicated that the adsorption capacity of activated sludge increased with decreasing initial pH and temperature.…”
Section: Sludgementioning
confidence: 99%